Kajian Perilaku Kuat Geser Tanah Terhadap Penambahan Serat Karung Goni - M. Martini; I. Fadliah; B. Biru (Civil Engineering Department, Tadulako University, 2023)
Soil improvement is a method to improve the physical and mechanical properties of soil that are not good. Soil improvement methods include chemical, mechanical, hydraulic, and reinforcement methods for example by adding geosynthetic sheets/fibers or steel rods. However, the use of these methods is relatively quite expensive from the aspect of the materials used when applied to small-scale volume work. This research tries to examine the behavior of the soil that is given the addition of jute sack fiber, especially to changes in shear strength/soil shear strength parameters. Jute sacks are an alternative material as a substitute for fiber of the Geosynthetic type, jute sacks have a rough texture made of jute fiber, where jute fiber is the second most used natural fiber after cotton. Jute fiber itself can be taken from the bark of the bast fiber tree. Jute itself is an environmentally friendly fabric because it is made from bio-degradable fibers and is included in fabrics made of 100% plant fibers. The percentage of jute fiber used was 0.25%, 0.50% and 0.75% of the dry weight of the soil with variations in length of 1.5 cm, 2.0 cm and 2.5 cm. The sample of soil tested is sandy type from the permanent residential area of Tondo, Mantikulore sub-district, Palu, Central Sulawesi. The addition of fiber has more effect on changes in the value of the soil friction angle than the value of cohesion. Jute fibers with lengths of 1.5 cm and 2.5 cm at percentages between 0.25% and 0.75% tend to increase, but at 2 cm length tend to decrease the value of shear strength. Fiber length and burlap percentage influence each other in increasing and decreasing the value of soil shear strength